Analisa Profile Matching Untuk Deccision Support System Pemilihan Staf Divisi Keuangan Perguruan Tinggi - Prawitasari, Dian; Setiawan, Aries; Ichwan Setiarso, Ichwan; Widjajanto, Budi; Setiawanta, Yulita; Pandji Mertha Agung Durya, Ngurah; Ernitawati, Yenny; Kusumaningrum, Lely Kusumaningrum (Jurnal Transformatika, 2025)
Some problems related to the finance division include delays in report preparation due to outdated data input, low competency in financial report preparation, suboptimal student payment services due to staff who are not familiar with student payment issues, lack of cooperation between staff resulting in work processes being hampered and staff competencies that are not appropriate to the job. Finance division staff need to meet several quality standards that include the relevance of study programs to sub-sections within the finance division, career reputation, interests, personality types, accuracy and trustworthiness. The benefit of this study is to provide an objective selection of finance division staff using the profile matching method to produce competent staff. The validation results in the form of long calculations and using the profile matching method were 0.89% which indicates that this method is able to provide support in the selection process of finance division staff.